Associations between migraine and possible risk factors in the Czech Republic - Riedlova, Petra; Zahradnikova, Barbora; Skybova, Dagmar; Slachtova, Hana; Jirik, Vitezslav; Tomaskova, Hana (Frontiers in neurology, 2023)
INTRODUCTION: Migraine is a widespread neurological disorder, growing increasingly common. However, the pathogenesis of the disease is often unclear and the evidence for the role of various risk factors is limited. This study aimed to identify risk factors associated with migraine and to contribute towards a better understanding of this disease. METHODS: Data from 3,247 questionnaires were analyzed for associations between migraine and sex, age, BMI, degree of education, and air pollution, along with other factors such as contact with friends, physical condition, health, anxiety, and depression. A cross-sectional study was conducted with an approximately equal distribution of the sample by age, gender and two analysed regions. Data were presented using basic descriptive statistics using the chi-square test. The model output was presented using a crude odds ratio (OR) and a fully adjusted OR. Three hundred and eight-six individuals (12%) suffered from migraine. RESULTS: In an adjusted model, the presented study found associations between the prevalence of migraine and sex, age, and level of education. Individuals with migraine statistically significantly more often suffered from depression, anxiety and other selected factors. However, the assumed significant association between the occurrence of migraine and pollution in the region has not been found.
Keywords: risk factors; anxiety; depression; air pollution; migraine